2009
DOI: 10.11606/issn.1981-0490.v12i2p157-171
|View full text |Cite
|
Sign up to set email alerts
|

LER e planos de demissão voluntária: trajetórias de dor e sofrimento entre bancários

Abstract: O artigo apresenta resultados obtidos em pesquisa realizada em 2002 com funcionários de um banco estatal de Ribeirão Preto, SP, que foram acometidos por Lesões por Esforços Repetitivos (LER). O objetivo da pesquisa foi conhecer o que determinou o adoecimento e quais foram as repercussões das LER no trabalho e na vida daqueles trabalhadores. Foram entrevistados 10 bancários (6 mulheres e 4 homens) com idades entre 41 e 49 anos. A seleção dos participantes levou em conta dois critérios: a) ser bancário com diagn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
24

Year Published

2011
2011
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 5 publications
0
3
0
24
Order By: Relevance
“…The disturbing existence of occupational diseases among bank employees reveals how organizational changes do not improve work conditions (22) . Such a fact is reported in the interviewees' reports: One of the studies that is referenced for the health of bank employees in Brazil (22) observed that the physical The sick leave also works as a social recognition of the disease (23) . Going back to work after being on sick leave (24) …”
Section: Guess That the Main Problem Today Is The Fear Bank Employementioning
confidence: 89%
“…The disturbing existence of occupational diseases among bank employees reveals how organizational changes do not improve work conditions (22) . Such a fact is reported in the interviewees' reports: One of the studies that is referenced for the health of bank employees in Brazil (22) observed that the physical The sick leave also works as a social recognition of the disease (23) . Going back to work after being on sick leave (24) …”
Section: Guess That the Main Problem Today Is The Fear Bank Employementioning
confidence: 89%
“…Isso porque as instituições financeiras foram precursoras no Brasil em adotar a automação e a informatização em seus procedimentos e, consequentemente, reestruturar sua produtividade. A reestruturação produtiva do setor bancário incluiu a utilização de novas tecnologias, a intensificação do ritmo de trabalho, a diversificação das tarefas, a adoção de novas formas de gestão, as terceirizações e as privatizações (Carrijo & Navarro, 2009;Paiva & Borges, 2009). Tais características acarretaram precarização laboral dos trabalhadores de bancos.…”
Section: Neoliberalismo E Governamentalidade Biopolíticaunclassified
“…On one side, they seek to understand the processes of subjectivation, including the psychological distress and illness (e.g. Carrijo and Navarro, 2009); on the other, they analyze the collective dimension of workers' actions, for example, investigating the power relationships or the collective ways of substantiation of work (Bernardo, 2009;Osório, 2006;Sato, 2002Sato, , 2012.…”
Section: Work and Daily Lifementioning
confidence: 99%